2016
DOI: 10.1016/j.psychres.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorders, but not cancer severity or treatment type, are risk factors for later generalised anxiety disorder and major depressive disorder in non metastatic breast cancer patients

Abstract: This study aimed to determine whether personality disorders were associated with later Major Depressive Disorder (MDD) or Generalised Anxiety Disorder (GAD) in breast cancer patients. This longitudinal and multicentric study included 120 French non-metastatic breast cancer patients. After cancer diagnosis (T1) and 7 months after diagnosis (T3), we assessed MDD and GAD (Mini International Neuropsychiatric Interview 5.0). We assessed personality disorders 3 months after diagnosis (VKP). We used multiple logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(51 reference statements)
1
10
0
2
Order By: Relevance
“…Emotional and total scores of the quality of life were found to be lowered by personality disorder, depressive disorder, having weaker coping mechanisms, and keeping self-accusatory personality traits in the forefront (38). The patients with breast cancer indicating the signs of personality disorders were found to be under a higher risk of having post-treatment generalized anxiety disorder and major depressive disorder (39). Moreover, a weak correlation was detected between the power of scale scores indicative of absence of affective behaviors or lack of confidence in subjective sensations and development of breast cancer (40).…”
Section: Discussionmentioning
confidence: 97%
“…Emotional and total scores of the quality of life were found to be lowered by personality disorder, depressive disorder, having weaker coping mechanisms, and keeping self-accusatory personality traits in the forefront (38). The patients with breast cancer indicating the signs of personality disorders were found to be under a higher risk of having post-treatment generalized anxiety disorder and major depressive disorder (39). Moreover, a weak correlation was detected between the power of scale scores indicative of absence of affective behaviors or lack of confidence in subjective sensations and development of breast cancer (40).…”
Section: Discussionmentioning
confidence: 97%
“… 8 11 Indeed, studies have postulated that women with breast cancer may have an increased risk of depression. 12 14 The therapeutic approach to breast cancer is based on a large body of evidence, 15 – 18 and there is increasing interest but still very limited data regarding attending psychiatric diseases in female patients with gynecologic, genital, and cervical cancer. 19 21 Patients suffering from different types of gynecologic cancer (genital/cervical cancer) may also have an increased risk of developing an attending psychiatric disease, but little is known about attending psychiatric disorders in patients with cancers other than breast cancer, such as gynecologic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies showed that in patients with cancer, low capacity for self-esteem and self-criticism are related to low acceptance of the disease and may result in anxiety. 26,43…”
Section: Discussionmentioning
confidence: 99%